Performing arts with children and teachers in pandemic times: What can teach us a blind dog? (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
his is a reflective-analytical report on a university extension project in performing arts pedagogy with children, their teachers and families, developed during the pandemic. The inducing theme was the adventures of a real female dog with multiple deficiencies, therefore, the video performances created articulate documentary material to the performing arts. Podcasts and written didactic material bring practical propositions and reflections on performing arts pedagogies with children. The products generated and their reach show the relevance of university extension in arts and education, as well as the meanings produced by the project in the initial training of undergraduates and in the continuing training of pedagogues.
Keywords: Performing arts; Children; Teachers; Pandemic; Extension